A POSTMODERNIST SELF-PORTRAIT IN KURT VONNEGUT’S BLUEBEARD - MAHADEVAN, S.; KARUNNITHI, V. (International Journal of Psychosocial Rehabilitation, 2020)
This paper examines Kurt Vonnegut’s Bluebeard which deals with the artistic renaissance of the abstract expressionist painter Rabo Karabekian through his hoax autobiography and his painting “Now It’s the Women’s Turn.” The title - “Bluebeard” receives attention together with the influence of abstract expressionism on the artistic development and personal vision of Rabo. Vonnegut’s use of metafictional devices in the novel in conjunction with the representational - abstract expressionist debate is one of the major critical concerns of the chapter. Rabo’s status as a survivor of the Turkish massacre of Armenians and World War is also elucidated. Autobiographical narratives of the aged receive special scrutiny. It opens into a general account of postmodernist narrative fiction and proceeds to examine the compulsions which shape Vonnegut’s fictional oeuvre. The persistence of postmodernist artifice in Bluebeard is an analogue for his moral vision of human possibilities and renewal and conquest of pain.